The molecular receptor NKBB enhances the persistence and anti-hepatocellular carcinoma activity of GPC3 CAR-T cells - Minghao Sui; Tiantian Liu; Xuanli Song; Ji Li; Han Ding; Yuqian Liu; Xinyu Wang; Huimin Liu; Yuchan Xue; Jianni Qi; Miao Zhang; Songbo Zhao; et al. (Pharmacological Research)
Chimeric antigen receptor (CAR) T cells have encouraging results in the treatment of hematological malignancies. However, CAR-T therapy still faces numerous challenges against solid tumors, such as hepatocellular carcinoma (HCC), owing to heterogeneous antigen expression in tumor cells, limited persistence of CAR-T cells, etc. Therefore, to treat HCC more effectively, we connected the molecular receptor NKBB to a second-generation glypican-3 (GPC3) CAR to construct GC3328z-NKBB CAR-T cells, which have double specific targets of GPC3 and NKG2DLs (natural killer group 2, member D ligands), dual co-stimulation of CD28 and 41BB, and a single CD3ζ chain. Our study showed that the molecular receptor NKBB conferred GPC3 CAR-T cells with enhanced migration and infiltration abilities towards HCC, higher central memory T (TCM) cell proportion and proliferation capacity, and reduced exhaustion level. GC3328z-NKBB CAR-T cells exhibited improved cytotoxicity against HCC cells and prolonged persistence. The cathepsin L/interleukin-17 (CTSL/IL-17) axis contributed to the superior anti-HCC activity of GC3328z-NKBB CAR-T cells. Overall, the molecular receptor NKBB significantly increased the persistence of GPC3 CAR-T cells, and GC3328z-NKBB CAR-T cells possessed potent anti-HCC activity in mice, providing a new strategy for the potential improvement of adoptive T cell therapy in the treatment of HCC.